An open-label, dose-ranging study of Rolontis, a novel long-acting myeloid growth factor, in breast cancer - Vacirca, J.; Chan, Arlene; Mezei, K.; Adoo, C.; Pápai, Z.; Mcgregor, K.; Okera, M.; Horváth, Z.; Landherr, L.; Hanslik, J.; Hager, S.; Ibrahim, E.; et al. (2018)
This randomized, open-label, active-controlled study investigated the safety and efficacy of three doses of Rolontis (eflapegrastim), a novel, long-acting myeloid growth factor, versus pegfilgrastim in breast cancer patients being treated with docetaxel and cyclophosphamide (TC). The primary efficacy endpoint was duration of severe neutropenia (DSN) during the first cycle of treatment. Patients who were candidates for adjuvant/neoadjuvant TC chemotherapy were eligible for participation. TC was administered on Day 1, followed by 45, 135, or 270 µg/kg Rolontis or 6 mg pegfilgrastim on Day 2. Complete blood counts were monitored daily when the absolute neutrophil count (ANC) fell to < 1.5 × 10 9 /L. Up to four cycles of TC were investigated. The difference in DSN (time from ANC < 0.5 × 10 9 /L to ANC recovery =2.0 × 10 9 /L) between the Rolontis and pegfilgrastim groups was -0.28 days (confidence interval [CI]: -0.56, -0.06) at 270 µg/kg, 0.14 days (CI: -0.28, 0.64) at 135 µg/kg, and 0.72 days (CI: 0.19, 1.27) at 45 µg/kg. Noninferiority to pegfilgrastim was demonstrated at 135 µg/kg (P = 0.002) and 270 µg/kg (P < .001), with superiority demonstrated at 270 µg/kg (0.03 days; P = 0.023). The most common treatment-related adverse events (AEs) were bone pain, myalgia, arthralgia, back pain, and elevated white blood cell counts, with similar incidences across groups. All doses of Rolontis were well tolerated, and no new or significant treatment-related toxicities were observed. In Cycle 1, Rolontis demonstrated noninferiority at the 135 µg/kg dose and statistical superiority in DSN at the 270 µg/kg dose when compared to pegfilgrastim.